2005
DOI: 10.1038/sj.ijo.0802988
|View full text |Cite
|
Sign up to set email alerts
|

Grape-seed derived procyanidins interfere with adipogenesis of 3T3-L1 cells at the onset of differentiation

Abstract: OBJECTIVE: Our group's previous results on the effects of a grape seed procyanidin extract (GSPE) on adipose metabolism showed that peroxisome proliferator-activated receptor-g (PPARg) plays a central role in the lipolytic effects of GSPE on adipocytes. Since PPARg2 is a main regulator of the differentiation process of adipocytes, we investigated whether GSPE affects the adipogenesis of 3T3-L1 cells. DESIGN: We performed a time point screening by treating 3T3-L1 cells with GSPE during the differentiation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 51 publications
7
52
1
Order By: Relevance
“…Procyanidins (oligomeric forms of catechins) are the most abundant polyphenols in red wine, apple and chocolate. Previous studies by our group showed that grape seed derived procyanidins (GSPE) limit adipocyte formation by altering the gene expression profile during in vitro adipocyte differentiation [1]. GSPE also decreased the mRNA levels of PPARc2 and HSL on fully differentiated 3T3-L1 adipocytes [2].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Procyanidins (oligomeric forms of catechins) are the most abundant polyphenols in red wine, apple and chocolate. Previous studies by our group showed that grape seed derived procyanidins (GSPE) limit adipocyte formation by altering the gene expression profile during in vitro adipocyte differentiation [1]. GSPE also decreased the mRNA levels of PPARc2 and HSL on fully differentiated 3T3-L1 adipocytes [2].…”
Section: Introductionmentioning
confidence: 87%
“…Quantitative RT-PCR Changes in the mRNA expression of selected adipocyte markers (PPARc2, HSL, C/EBPa and Pref-1) [1] were analysed by quantitative PCR. Briefly, 1 mg of total RNA was reverse transcribed by the SuperScript II Rnase H_Reverse Transcriptase (LifeTechnologies).…”
Section: Animal Experimental Proceduresmentioning
confidence: 99%
“…Amino acids L-proline (Pro) and L-Hyp were purchased from Wako Chemicals, Osaka, Japan. 200 ng/mL Pro-Hyp (the Pro-Hyp group) or a mixture of Pro and Hyp (200 ng/mL each; the Pro/Hyp group) was added to the medium every 2 days according to the method of Pinent et al (2005) and Kim sisting of 15 sec at 95℃ and 1 min at 60℃. The Ct value obtained by amplification of each target was compared among the samples after normalization using GAPDH expression levels.…”
Section: Methodsmentioning
confidence: 99%
“…These studies suggest that Pro-Hyp is one of the physiologically active oligopeptides derived from ingested CP. 3T3-L1 is a mouse preadipocyte line cell frequently used for studies on the differentiation of preadipocytes in vitro, since they differentiate and mature to produce triacylglycerides upon stimulation with insulin, dexamethasone and isobutylmethylxanthine (Pinent et al, 2005). In this study, we investigated the effects of Pro-Hyp on differentiation of 3T3-L1 cells in vitro in order to examine whether a digested product of ingested CP modulates the functions of adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they are strong antioxidants [2,3], inhibit tumor formation [4], improve endothelial function [5,6] and affect energy metabolism [7]. To elucidate the molecular mechanisms explaining the beneficial effects of flavonoids observed in vivo, several studies have employed a systems biology approach with transcriptomics and proteomics techniques, using cell culture systems [8][9][10][11][12][13][14][15][16][17][18]. However, these in vitro studies may have generated misleading findings due to the non-physiological exposure conditions mostly used.…”
Section: Introductionmentioning
confidence: 99%